Determination of Water Quality Parameters of Bⁿyⁿk Menderes River, Turkey - Dagdelen, Necdet; Yesilirmak, Ercan; M. Akτay, Selin; Sezgin, Fuat (Asian Journal of Chemistry, 2010)
In this study, seasonal averages of some chemical constituents at upper and lower six monitoring stations in Büyük Menderes river were investigated. These water quality parameters are electical conductivity (EC), sodium, chloride, chemical oxygen demand (COD), boron and sodium absorption rate (SAR). Laboratoary analyses for water samples were conducted at State Hydraulic Works of Turkey DSI's Quality Control and Laboratory Department in Aydin. In the result of the research, there have been differencies for chemical contents between sampling stations. However seasonal changes have also been worth taking into consideration. While pollution has been arising more and more in upstream (Sarayköy and Çubukdag bridges), there have been clear increases especially electrical conductivity boron, sodium chloride, chemical oxygen demand (COD) and sodium absorption rate (SAR). Especially, increasing level in COD and boron values at upstream stations suggest that water quality of Büyük Menderes river has been deteriorated in terms of organic and geothermal pollution from industries and residential areas. It is expected that the results of this study not only provide the information to the public with the recent change in water quality of Büyük Menderes river quantitatively but also help in establishing future management strategies.